EFFECTIVENESS OF TRAINING ACTIVITIES AT THE TRAINING CENTER AND COMMUNITY EMPOWERMENT IN RURAL, UNDERDEVELOPED AND TRANS-SETTLEMENT AREAS IN MAKASSAR - Arsyat; Sitti Haerani; Haeriah Hakim (CV. Radja Publika, 2023)
The aim of this research is to evaluate the effectiveness of training conducted at the hall. A quantitative approach is used for the study, focusing on the population of 103 training alumni from Balai Pelatihan dan Pemberdayaan Masyarakat Desa, Daerah Tertinggal dan Transmigrasi Makassar. Data is collected through a survey in the form of a questionnaire and analyzed using the SPSS application. The results of the study show that the training organized by Balai Pelatihan dan Pemberdayaan Masyarakat Desa, Daerah Tertinggal dan Transmigrasi Makassar is highly effective. Among the three effectiveness indicators used, one indicator shows effective results, specifically related to the assessment of training facilities and amenities. The other two indicators show highly effective results, particularly concerning the evaluation of training materials and the assessment of training trainers.